The Influences on Practice in Social Care: An Australian Study. Issue 1 (1st January 2019) - Darracott, Rosalyn; Lonne, Bob; Cheers, Brian; Wagner, Ingrid
ABSTRACT: Much of the discourse regarding social care practice focuses on the differences between the various professions, practice fields, geographical, and organizational contexts involved in the provision of social care. This study surveyed Australian social care practitioners' ( N = 438) perceptions of influence on their practice and what similarities and differences existed in these perceptions. Eighteen influential factors were identified with minimal differences across the participants' profession, practice field, organizational sector, or geographical context. These findings suggest that a common ground of experience exists that can be used as a basis for critical discussions and interdisciplinary practice and, thereby, provide a foundation for more consistent and integrated service delivery and outcomes.